KOORDINASI PENGAWAS DAN KEPALA SEKOLAH DALAM PELAKSANAAN SUPERVISI PENDIDIKAN PADA SD NEGERI LAMPEUNEURUT KABUPATEN ACEH BESAR - Munawarah, Nasir Usman, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: A good quality of education could be achieved through various factors and one of them is to create a good coordination and mutual understanding between the school-supervisor and principal in implementing the supervision of education. Such condition would lead to a more conducive teaching process, building a mutual understanding, meaningful and harmony between the two parties. The objective of this study is to know the coordination between school supervisors and principals in: (1) planning, (2) implementing, (3) carrying out the follow-up programs related to the supervision of education. The approach applied in this study was qualitative and descriptive methodologies. Data were collected and obtained through interviews, observation, and documentation studies. School-supervisor and principal of an elementary school (referred as SD Negeri in bahasa) in the Lampeuneurut area were applied as subjects. Results showed that: (1) a good coordination existed between the school-supervisor and principals by the planning of supervision program in education, including by the planning of various capacity building programs aiming to strengthen the teachers’ capacity and professionalism. However, supervision programs have not yet been agreed with the vision, mission, and objectives of the involved school, (2) a diverse techniques in supervision program between the supervisor and principal were applied by the implementation, e.g. observation, personal and formal meetings. However, these were acknowledged as insufficient and ineffective, especially the time was presumed as the most limiting factor by the guidance and supervision among teachers, (3) the follow-up programs were planned and carried out in two ways: (i) direct feedback in a formal meeting involving individual teacher and supervisor, or (ii) indirect ways e.g. general meeting with the whole school staff. However, the supervision results had not yet been programmed in systematically and details. Thus, there had been no formal documentation regarding the follow-up programs based on the previous supervision.Keywords: Coordination, Supervisor and Educational Supervision Abstrak: Pendidikan bermutu tercipta apabila koordinasi pengawas dan kepala sekolah dalam melaksanakan supervisi pendidikan dilakukan secara harmonis, maka akan tercipta suasana proses belajar mengajar yang bermakna dan menyenangkan. Tujuan penelitian ini adalah untuk mengetahui koordinasi pengawas dan kepala sekolah dalam: (1) Menyusun program supervisi pendidikan; (2) Implementasi program supervisi pendidikan dan (3) Melaksanakan tindak lanjut hasil supervisi pendidikan. Pendekatan yang digunakan adalah kualitatif dengan metode deskriptif, teknik pengumpulan data dilakukan melalui pedoman wawancara, observasi, dan studi dokumentasi. Subjek penelitian adalah pengawas dan kepala sekolah. Hasil penelitian menunjukkan bahwa: (1) Pengawas dan kepala SD Negeri Lampeuneurut telah menunjukkan koordinasi yang baik dalam menyusun program supervisi pendidikan, program supervisi pendidikan berisi kegiatan peningkatkan kompetensi profesionalisme guru, namun program supervisi masih kurang mengacu pada visi, misi dan tujuan sekolah binaan. (2) Koordinasi pengawas dan kepala sekolah dalam implementasi supervisi dilakukan sesuai dengan program supervisi melalui teknik supervisi yaitu: observasi, pertemuan pribadi dan rapat, akan tetapi waktu yang tersedia dalam pembinaan dan bimbingan guru masih belum merata serta efektif; (3) Koordinasi pengawas dan kepala sekolah dalam tindak lanjut hasil implementasi supervisi pendidikan dilakukan dengan cara langsung memberikan umpan balik melalui pertemuan individu guru yang disupervisi dan secara tidak langsung melaui rapat dengan staf sekolah, namun demikian hasil supervisi tidak terprogram dan terperinci. Dokumentasi hasil laporan tindak lanjut supervisi pendidikan tidak ada.Kata Kunci: Koordinasi, Pengawas dan Supervisi Pendidikan